Insight Into the Role of Ferroptosis in Non-neoplastic Neurological Diseases - Lei, Jianwei; Chen, Zhihua; Song, Shuxin; Sheng, Chunpeng; Song, Sihui; Zhu, Jianming (Frontiers in Cellular Neuroscience, 2020)
Ferroptosis is an iron-dependent form of cell death characterized by the accumulation of intracellular lipid reactive oxygen species. Ferroptosis is significantly different from other types of cell death including apoptosis, autophagy, and necrosis, both in morphology and biochemical characteristics. The mechanisms that are associated with ferroptosis include iron metabolism, lipid oxidation and other pathophysiological changes. Ferroptosis inducers or inhibitors can influence its occurrence through different pathways. Ferroptosis was initially discovered in tumors, though recent studies have confirmed that it is also closely related to a variety of neurological diseases include neurodegenerative disease (Alzheimer's disease, Parkinson's disease etc.) and stroke. This article reviews the definition and characteristics of ferroptosis, the potential mechanisms associated with its development, inducers/inhibitors, and its role in non-neoplastic neurological diseases. We hope to provide a theoretical basis and novel treatment strategies for treatment of central nervous system diseases by targeting ferroptosis.